Agricultural Chemistry - Stoytcheva, Margarita; Zlatev, Roumen (IntechOpen, 2013)
The present book is a collection of ten original research articles and reports, associated with selected topics in agricultural chemistry. The discussed issues are organized in four sections: Classification and labeling of active substances in plant protection products, Environmental and stress plant physiology and behavior, Antimicrobial and antioxidant potential of plant extracts, and Pollutants analysis and effects. The information provided in this book should be of interest for academic researchers and for agriculturalists.